Functional reagent, preparation method thereof and application of functional reagent in conductive glass substrate recovery
The recycling of TCO glass using a mixed solvent of chelating agent and chlorobenzene organic solvent solves the problems of high TCO glass recycling cost and harmful substances produced in the existing technology, realizes efficient, non-toxic and low-cost recycling of conductive glass substrate, maintains photoelectric conversion efficiency, and is suitable for the industrial application of perovskite batteries.
Patent Information
- Application Number
- CN202510529583.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-09-12
AI Technical Summary
Existing TCO glass recycling technology has the disadvantages of high cost, complex process and generation of hazardous substances, making it difficult to achieve efficient, non-toxic and low-cost recycling.
A mixed solvent of a chelating agent and a chlorobenzene organic solvent is used as a functional reagent, and the conductive glass substrate is recovered through microwave ultrasound and cleaning steps. The preparation process is simple and the conductive glass substrate can be reused many times.
The efficient recycling of the conductive glass substrate is achieved, the photoelectric conversion efficiency is maintained, the process is simple and easy to industrialize, it is environmentally friendly, and the solvent can be recycled multiple times.
Smart Images

Figure CN120624138A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic photovoltaic cell devices, and particularly relates to a functional reagent, a preparation method thereof, and an application thereof in the recovery of conductive glass substrates. Background Art
[0002] Perovskite cells (PSCs) are solar cells that are broadly composed of five layers: a transparent electrode (metallic, such as gold or silver), a hole transport layer (HTL), a perovskite thin film layer, an electron transport layer (ETL), and a transparent conductive glass layer (TCO). The TCO glass serves as a carrier, transmits light, and conducts electricity. However, it is costly, challenging to obtain certification, and requires collaborative R&D with downstream customers. Furthermore, the process is primarily controlled by overseas companies, resulting in high procurement costs. Therefore, TCO glass recycling is becoming increasingly important and is a key area of perovskite cell recycling technology.
[0003] Chinese patent application CN101562212A discloses a method for recycling and reusing transparent conductive glass substrates for solar cells. This method uses an etching medium to selectively etch defective solar cells that have failed in the manufacturing process. The etching medium etches the failed layer at a much higher rate than the transparent conductive glass layer and the glass substrate. This allows the etching medium to generally only etch and remove the failed layer, leaving the glass substrate and the transparent conductive glass layer for recycling and reuse. However, this technology involves multiple recycling processes, and the etching medium used in this method is an organic solvent such as sodium hydroxide, potassium hydroxide, lithium hydroxide, carbon tetrachloride, sulfur hexafluoride, bromine fluoride, and cesium hydroxide. These etching media easily produce harmful substances during the reaction, which is not conducive to green recycling management and is relatively costly. Another example is a paper published in Advanced Functional Materials by G. Grancini and his team at the University of Pavia titled "Sustainable and Circular Management of Perovskite Solar Cells via Green Recycling of Electron Transport Layer-Coated Transparent Conductive Oxide." In this work, they used dimethyl sulfoxide (DMSO) as a green solvent to dissolve the upper layer of the device, refurbishing the tin oxide (SnO2)-coated indium tin oxide glass from a nip PSC. Using the recycled substrate, they produced a new generation of PSCs that maintained the same power conversion efficiency (PCE) of 22.6% as the new sample and exhibited a higher average PCE. However, the large amount of DMSO used in this study can interact with hydrophobic groups in proteins, leading to protein denaturation and potentially vascular, hepatotoxic, and renal toxicity to operators. Furthermore, DMSO can dissolve a large number of substances, making it difficult to separate the subsequent transport and absorber layers.
[0004] Therefore, it is particularly important to use a simple, non-toxic and low-cost process to recycle TCO glass in devices. Summary of the Invention
[0005] In response to the problems existing in the prior art, the present invention provides a functional reagent and a preparation method thereof, as well as an application in the recycling of conductive glass substrates. The functional reagent can be repeatedly recycled and has a simple preparation process. After recycling, the photoelectric conversion efficiency of the original battery can still be maintained.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] In one aspect, the present invention provides a functional agent, wherein the functional agent is a mixed solvent obtained from a chelating agent and a chlorobenzene organic solvent.
[0008] Preferably, the chelating agent is selected from at least one of sodium thiocarbamates, carboxylic acids, polyphosphates, aminocarboxylic acids, 1,3-diketones, hydroxycarboxylic acids, polyamines and amides.
[0009] Preferably, the concentration of the chelating agent is 0.001 mg / mL-500 mg / mL.
[0010] More preferably, the concentration of the chelating agent is 5 mg / mL-15 mg / mL.
[0011] Preferably, the chelating agent is sodium dimethyldithiocarbamate or sodium citrate.
[0012] Preferably, the concentration of the sodium dimethyldithiocarbamate is 7.1 mg / mL-14.3 mg / mL; the concentration of the sodium citrate is 5.1 mg / mL-15 mg / mL.
[0013] More preferably, the concentration of the sodium dimethyldithiocarbamate is 7.15 mg / mL, and the concentration of the sodium citrate is 12.9 mg / mL.
[0014] Preferably, the chlorobenzene organic solvent is selected from at least one of chlorobenzene, ethanol, ether and propanol.
[0015] Preferably, the functional agent can be applied to perovskite cells with an upright structure or an inverted structure.
[0016] The present invention also provides a method for preparing the functional reagent, which comprises mixing the chelating agent with water and then mixing the mixture with chlorobenzene organic solvent to obtain the functional reagent.
[0017] Specifically, the functional reagent is prepared by first disposing the chelating agent in an aqueous solution and stirring the solution, and then adding a certain amount of chlorobenzene solvent thereto. When the solution is allowed to stand, upper and lower layers will be formed due to different densities.
[0018] On the other hand, the present invention provides a use of the above functional reagent or the functional reagent prepared by the above preparation method in the recovery of conductive glass substrates.
[0019] The present invention also provides a process for recycling a conductive glass substrate, comprising the following steps: immersing a degraded perovskite cell in the above-mentioned functional reagent, followed by ultrasonic treatment and cleaning to obtain the conductive glass substrate.
[0020] Preferably, the ultrasound is microwave ultrasound, and the conditions of the microwave ultrasound are: temperature of 20° C.-60° C., and time of 5-60 min.
[0021] Further preferably, the microwave ultrasound conditions are: temperature 20-25° C., time 2-10 min.
[0022] Most preferably, the microwave ultrasound conditions are: temperature 25°C, time 5 min.
[0023] Specifically, cleaning involves removing the perovskite, organic materials in the transport layer, and metal electrodes covering the conductive glass substrate, thereby leaving an oxide-rich conductive glass substrate or pure conductive glass. This process involves sequentially cleaning the surface with water and ethanol, followed by a 15-30 minute ozone cleaning step in an ozone cleaner before proceeding to battery assembly.
[0024] The present invention also provides an application of the above functional reagent or the functional reagent prepared by the above preparation method in improving the conductive properties of a conductive glass substrate.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The reagents and drugs used in the recovery process steps of the present invention are readily available, and the control and recycling of the lead source can be achieved by controlling different chelating systems.
[0027] (2) The recycling process of the present invention can obtain a clean conductive glass substrate in just one step. The process is simple and easy to industrialize, and the solvent can be recycled multiple times.
[0028] (3) The functional reagent of the present invention can be repeatedly used and recycled. When the cleaning effect is saturated, the chlorobenzene solution containing the organic transmission material can be separated by extraction. The chlorobenzene can be recovered by low-temperature heating and reused again. In addition, since the density of chlorobenzene is greater than that of water, the volatilization of chlorobenzene by water is effectively suppressed, thereby reducing the loss of chlorobenzene and achieving the effect of environmental protection.
[0029] (4) The conductive glass substrate recovered by the functional reagent of the present invention can still maintain the photoelectric conversion efficiency of the original battery after being assembled into a complete battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Flowchart of an embodiment of the present invention.
[0031] Figure 2 This is the appearance of the perovskite cell after cleaning with the first solvent in Example 1 of the present invention.
[0032] Figure 3 This is a surface SEM image of the glass substrate after cleaning with the first solvent in Example 1 of the present invention.
[0033] Figure 4This is the appearance of the perovskite cell after solvent cleaning in Example 2 of the present invention.
[0034] Figure 5 This is a surface SEM image of the glass substrate after cleaning in Example 2 of the present invention.
[0035] Figure 6 This is the appearance of the perovskite cell after cleaning according to Example 3 of the present invention.
[0036] Figure 7 This is a surface SEM image of the glass substrate after cleaning in Example 3 of the present invention.
[0037] Figure 8 This is the appearance of the perovskite cell after cleaning in comparative example 1.
[0038] Figure 9 This is the appearance of the perovskite cell after cleaning in comparative example 2.
[0039] Figure 10 This is the surface morphology of the original conductive glass ITO film of the present invention. DETAILED DESCRIPTION
[0040] The present invention is described below through specific embodiments to make the technical solution of the present invention easier to understand and grasp, but the present invention is not limited thereto. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0041] The endpoints and any value of the scope disclosed in this article are not limited to this accurate scope or value, and these scopes or values should be understood as comprising values close to these scopes or values.For numerical range, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between the separate point value, can be combined with each other and obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article. Unless the context clearly indicates otherwise, the singular form "one", "a kind of" and "described" as used herein include singular and plural indicators. The numerical range stated by endpoint is included in all numerical values and fractions within the corresponding range, and the stated endpoint.
[0042] Based on the embodiments of the present invention, all other embodiments obtained by persons of ordinary skill in the art without inventive effort shall fall within the scope of protection of the present invention. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0043] Experimental raw material information:
[0044] SnO2 solution (15 wt% aqueous solution), lead iodide (PbI2, 99.9%), and N,N-dimethylformamide (DMF, 99.9%) were purchased from Alfa-Aesar; lead bromide (PbBr2, 99.9%), dimethyl sulfoxide (DMSO, 99.5%), cesium iodide (CsI, 99%), and chlorobenzene (CB, 99.5%) were purchased from Sigma-Aldrich; methylamine bromide (MABr, 99.9%), formamidine iodide (FAI, 99.9%), Spiro-OMeTAD, and 4-tert-butylpyridine (t-BP) were purchased from Xi'an Biolight; sodium citrate (C6H5Na3O7) (90%) was purchased from Titan Reagent Platform; and sodium dimethyldithiocarbamate (C3H6NNaS2) was purchased from Adamas (98%+, Titan Reagent Platform). None of the materials used were further processed.
[0045] Preparation of original perovskite cells:
[0046] 1. Prepare a 1.4 mol / mL perovskite solution: weigh 545.4 mg of PbI2, 79.6 mg of PbBr2, 195.0 mg of FAI, 18.1 mg of CsI, and 21.9 mg of MABr, mix them, and dissolve them in 1 mL of DMF:DMSO (volume ratio 7:3). Then, heat and stir at 60°C for 1 hour.
[0047] 2. Preparation of original SnO2 film: Prepare 10 mL of 5 wt% SnO2 aqueous solution, then spin-coat it on the conductive glass ITO, and calcine it at 150°C for 30 minutes to form a SnO2 film.
[0048] 3. 30-50 μL of the perovskite solution is then spin-coated onto the pristine SnO2 film substrate using a toluene anti-solvent process to form the corresponding perovskite absorber film. After cooling, the modified Spiro-OMeTAD chlorobenzene solution is spin-coated. After air drying, an 80 nm thick silver electrode is evaporated to form the pristine perovskite solar cell.
[0049] Through the solar simulator, at 100mW cm -2 The photoelectric conversion efficiency was tested under standard light. The effective area of the cell is 0.0625 cm 2 .
[0050] Example 1
[0051] 1. Preparation of functional reagent: 2 mmol of sodium dimethyldithiocarbamate was dissolved in 20 ml of aqueous solution, and then 20 ml of chlorobenzene solution was added to make the chelating agent concentration 7.15 mg / mL to obtain the functional reagent.
[0052] 2. Recycling and Cleaning: After the original perovskite cell is placed at room temperature with a humidity of 80% ± 5% for 5 days, a certain degree of decomposition will occur. The decomposed perovskite cell is placed in the above-mentioned functional reagent solution and ultrasonicated for 5 minutes. The TCO glass sheet is removed and ultrasonically cleaned with water and ethanol for 3 minutes in sequence to obtain TCO glass containing SnO2 oxide, i.e., the conductive glass substrate.
[0053] 3. Reuse: The TCO glass conductive substrate of the recycled SnO2 oxide is cleaned in an ozone cleaner for 20 minutes, and then the perovskite solution and subsequent hole layer are spin-coated according to the preparation process of the original perovskite cell, and the upper electrode is evaporated to assemble into a complete cell.
[0054] Example 2
[0055] The only difference from Example 1 is the preparation of the functional reagent in step 1: 2 mmol of sodium citrate is dissolved in 20 ml of aqueous solution, followed by the addition of 20 ml of chlorobenzene solution to a concentration of 12.9 mg / mL to obtain the functional reagent. All other steps are the same as in Example 1.
[0056] Example 3
[0057] The only difference from Example 1 is the preparation of the functional reagent in step 1: 2.0 mmol of sodium dimethyldithiocarbamate was dissolved in 20 ml of aqueous solution, followed by the addition of 20 ml of ethanol solution to a chelating agent concentration of 7.15 mg / mL to obtain the functional reagent. All other steps were the same as in Example 1.
[0058] Comparative Example 1
[0059] Compared with Example 1, the only difference is the preparation of the functional reagent in step 1, specifically, taking 20 ml of chlorobenzene solution as the functional reagent. The other steps are the same as in Example 1.
[0060] Comparative Example 2
[0061] The only difference from Example 1 is the preparation of the functional reagent in step 1, specifically, 2.0 mmol of sodium dimethyldithiocarbamate was dissolved in 20 ml of aqueous solution to a chelating agent concentration of 7.15 mg / mL. The other steps were the same as in Example 1.
[0062] Comparative Example 3
[0063] The only difference from Example 1 was the preparation of the functional reagent in step 1, specifically, 2.0 mmol of sodium dimethyldithiocarbamate was dissolved in 20 ml of aqueous solution, followed by the addition of 60 ml of chlorobenzene solution to a chelating agent concentration of 3.575 mg / mL. All other steps were the same as in Example 1.
[0064] Test Case
[0065] Photoelectric conversion efficiency test
[0066] Through the solar simulator, at 100mW cm -2 Under standard light, the photoelectric conversion efficiency of the cells of Examples 1-3 and Comparative Examples 1-3 was tested. The results are shown in Table 1.
[0067] Table 1. Photoelectric conversion performance results of the battery of the embodiment and the comparative example
[0068]
[0069]
[0070] The results in the table above show that compared to the original perovskite cells, the photoelectric conversion efficiency of the SnO2-based cells recovered in the examples of the present invention maintained 96.7% of the original efficiency, even exceeding 98%, still comparable to and catching up with the original perovskite cells. However, when the cleaning agent concentration used in Comparative Example 3 is outside the scope of protection of the present invention, the photoelectric conversion efficiency can only maintain 86% of the original efficiency, failing to reach 90%, affecting the recovery quality.
[0071] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A functional reagent, characterized in that: The functional reagent is a mixed solvent obtained from a chelating agent and a chlorobenzene organic solvent.
2. The functional reagent according to claim 1, characterized in that: The chelating agent is selected from at least one of sodium thiocarbamate salts, carboxylic acids, polyphosphates, aminocarboxylic acids, 1,3-diketones, hydroxycarboxylic acids, polyamines and amides; and the concentration of the chelating agent is 0.001 mg / mL-500 mg / mL.
3. The functional reagent according to claim 2, characterized in that: The chelating agent is sodium dimethyldithiocarbamate or sodium citrate; the concentration of the sodium dimethyldithiocarbamate is 7.1 mg / mL-14.3 mg / mL; the concentration of the sodium citrate is 5.1 mg / mL-15 mg / mL.
4. The functional reagent according to claim 3, characterized in that: The concentration of the sodium dimethyldithiocarbamate is 7.15 mg / mL; the concentration of the sodium citrate is 12.9 mg / mL.
5. The functional reagent according to claim 1, characterized in that: The chlorobenzene organic solvent is selected from at least one of chlorobenzene, ethanol, ether and propanol.
6. A method for preparing the functional reagent according to any one of claims 1 to 5, characterized in that: The functional reagent is obtained by mixing the chelating agent with water and then mixing it with chlorobenzene organic solvent.
7. Use of the functional reagent according to any one of claims 1 to 5 or the functional reagent prepared by the preparation method according to claim 6 in the recovery of conductive glass substrates.
8. A process for recycling a conductive glass substrate, characterized in that: The following steps are involved: The degraded perovskite cell is immersed in the functional reagent according to any one of claims 1 to 5, and then ultrasonicated and cleaned to obtain the conductive glass substrate.
9. The process according to claim 8, characterized in that: The ultrasound is microwave ultrasound, and the conditions of the microwave ultrasound are: temperature of 20° C.-60° C., and time of 5-60 min.
10. Use of the functional agent according to any one of claims 1 to 5 or the functional agent prepared by the preparation method according to claim 6 in improving the electrical conductivity of a conductive glass substrate.
Citation Information
Patent Citations
Method for recycling transparent conducting glass substrate of solar cell
CN101562212A